Calibration of pyroelectric infrared detectors using a light bulb as a black body radiation source - S. Pakluea (2020)
© Published under licence by IOP Publishing Ltd. The pyroelectric detector is used for measuring infrared radiation. It has uniform response covering wide wavelength from 0.001 m to 1000 m and can measure the high-power level of radiation at room temperature operation. In this research, we calibrated the pyroelectric detector by using a tungsten light bulb as an infrared source. Properties of blackbody radiation from the light bulb are investigated. The interested properties include the spectral distribution and the relation of radiation intensity to heating temperature. The most radiation emitted from the light bulb lies in infrared wavelength. The pyroelectric detectors were calibrated against a pyroelectric Joulemeter with known responsivity. The results of this study will be applied to the measure of the radiation produced from the accelerator-base radiation source at the PBP-CMU Electron Linac Laboratory.